Blackstone's Statutes on Company Law 2021-2022 - Derek French (United Kingdom Oxford University Press, 2021)
Unsurpassed in authority, reliability and accuracy; the 2021-2022 edition has been fully revised and updated to incorporate all relevant legislation for company law courses. Blackstone's Statutes on Company Law is an abridged collection of legislation carefully reviewed and selected by Derek French. With unparalleled coverage of company law, Blackstone's Statutes on Company Law leads the market: consistently recommended by lecturers and relied on by students for exam and course use. Blackstone's Statutes on Company Law is: - Trusted: ideal for exam use - Practical: find what you need instantly - Reliable: current, comprehensive coverage - Relevant: content reviewed to match your course
Keywords: Company law; Law; (ASB-2400) Law for Business